Effect of protopine on cytosolic Ca2+ in rabbit platelets - Shen Zhi-qiang; Chen Zhi-he; Duan Li (Acta Pharmacologica Sinica, 2016)
AIM: To study the influence of protopine (Pro) on the cytoplasmic free Ca2+ concentration ([Ca2+]i) in rabbit platelets. METHODS: Measurement of [Ca2+]i of platelets in vitro by Fura 2-AM fluorescence technique. RESULTS: In the presence of CaCl2 1 mmol.L-1, Pro 10, 20, and 40 mumol.L-1 attenuated the rise in [Ca2+]i evoked by ADP from (420 +/- 57) to (320 +/- 26), (264 +/- 21), and (180 +/- 14) nmol.L-1, respectively, by arachidonic acid (AA) from (280 +/- 36) to (210 +/- 17), (184 +/- 21), and (143 +/- 16) nmol.L-1, respectively, and by platelet-activating factor (PAF) from (350 +/- 42) to (282 +/- 31), (223 +/- 30), and (165 +/- 15) nmol.L-1, respectively. In the presence of egtazic acid 1 mmol.L-1, Pro 10, 20, and 40 mumol.L-1 reduced the Ca2+ release induced by ADP, AA, and PAF, respectively. Pro 10, 20, and 40 mumol.L-1 also decreased ADP-, AA-, and PAF-induced Ca2+ influx. CONCLUSION: Pro inhibited not only Ca2+ release but also the influx of Ca2+.